MANAGEMENT OF DIARRHEA IN CHILDREN AND ITS RELATION TO STUNTING - adenina, syarinta; Tamzil, Nia Savitri (Healthy Tadulako Journal (Jurnal Kesehatan Tadulako), 2024)
Diarrhea is a condition of changing bowel movements accompanied by an increase in the frequency of diarrhea. Currently, the incidence and death cases due to diarrhea in Indonesia are still very high and need special attention, especially for clinicians. The conditions of diarrhea and stunting are related to each other. Prolonged diarrhea will cause stunting, while children with stunting will easily experience diarrhea. Therefore, further understanding is needed as a reference in managing diarrhea. Literature searches were obtained from various online portals such as Medscape, Pubmed, google scholar, and science direct using the keywords “diarrhea” “children” and “stunting”. Management diarrhea is mainly by rehydration, micronutrients (vitamin A, folic acid, iron, vitamin B12, and zinc), probiotics, antisecretory, and antibiotics. A comprehensive therapeutic approach is needed to avoid diarrhea complications as well as treatment options specifically for cases of diarrhea in children with stunting.